Case report: delirium and hypothyroidism: Klinični primer: delirij in hipotiroidizem - Plemenitaš Ilješ, Anja (Acta Medico-Biotechnica, 2021)
Purpose: The purpose of this report is to present a clinical case of an elderly female patient with complex delirium suffering from hypothyroidism with a clinical manifestation of psychosis. Case report: After a preliminary diagnosis of acute confusion, a 70-year-old female patient was treated in the Centre for Emergency Medicine, Community Health Center and then by internists and neurologists. Afterwards, she was admitted to the Department of Psychiatry due to unexplained delirium. Acute hypothyroidism was detected upon further diagnosis. The patient was identified as suffering from acute hypothyroidism with an underlying cognitive decline. Conclusion: Hypothyroidism can present as changes in mental status and cognition, which can have a clinical manifestation of delirium and later psychosis that is also known as “myxedema madness”. This clinical case was treated causally with thyroid hormones and symptomatically first with clomethiazole and later with risperidone.